ECONOMIC BURDEN OF CARDIOVASCULAR DISEASES IN THE RUSSIAN FEDERATION IN 2016 - A. N. Kontsevaya; O. M. Drapkina; Yu. A. Balanova; A. E. Imaeva; E. I. Suvorova; M. B. Khudyakov (Рациональная фармакотерапия в кардиологии, 2018)
Aim. To evaluate the economic burden of cardiovascular diseases (CVD) in the Russian Federation (RF) in 2016, including the direct costs and the economic losses caused by reduced productivity.Material and methods. Main data sources: data of the Federal state statistics service, data of state statistical reporting (forms №14, №141, №12 and №16-VN), and data of State Guarantee Program of Free Medical Care to the Citizens of the RF, statistical data of CVD, ischemic heart disease (IHD), myocardial infarction, cerebrovascular diseases, stroke. The direct medical costs were calculated based on the number of hospitalizations, including daycare center, emergency calls and outpatient visits due to CVD using the costs of the State Guarantee Program. The amount of disability benefits payments was calculated based on the number of disabled persons from each group and by the amount of the disability allowance. Indirect costs (economic losses) included a shortage of gross domestic product (GDP) due to premature mortality and disability in economically active age and loss of earnings due to temporary incapacity for work. The potential years of life lost (PYLL) were calculated using the number of life years not reached in economically active age due to premature death. Losses associated with premature mortality in the economically active age included unproduced GDP due to lost life years in the corresponding age group due to deaths from CVD, meaning the population’ employment rate. Statistical analysis was performed by Microsoft Excel 10.0.Results. PYLL due to premature death from CVD – 4.5 million years of potential life in economically active age, mostly men (3.3 million PYLL). Among almost 50% of men PYLL were due to ischemic heart disease. Economic burden because of CVD in 2016 in the RF reached 2.7 trillion ₽, which is equivalent of 3.2% of GDP for this year. In the structure of burden among all blood circulatory system diseases, IHD was in the first place (over 1 trillion ₽). In the burden structure, direct costs were only 8.1%, losses in the economics – 91.9% of the total burden. In the cumulative burden of CVD, IHD determined as 39.8% (over a trillion ₽), cerebrovascular diseases – fifth part (560 billion ₽), strokes and heart attacks – 424 billion ₽ and 213.1 billion ₽, respectively.Conclusion. The economic burden because of CVD in the RF in 2016 was 2.7 trillion ₽ (3.2% of GDP). Economic losses caused by premature mortality of people in economically active age prevailed in the structure of the burden (over 90%). Such the significant economic burden is a weighty argument for increasing investments in the prevention and treatment of CVD.